ЕЩЕ РАЗ О КОНТАМИНАЦИОННОМ СЛОВООБРАЗОВАНИИ В РУССКОМ ЯЗЫКЕ - ХАБИБУЛЛИНА, ЕЛЕНА (Studia Rossica Posnaniensia, 2006)
The article considers features of contaminational word formation in modem Russian. Special attention is given to its punning version in correspondence with word formation stylistics and sociolinguistics.